The Poetics of Engagement: Improvisation, Musical Communities, and the COVID-19 Pandemic - Fischlin, Daniel; Risk, Laura; Stewart, Jesse (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
The COVID-19 pandemic turned the music industry upside-down overnight and impacted music-making at all levels. In these special issues, we invited musicians, performers, scholars, arts presenters, and other cultural workers to reflect on the extraordinary challenges posed by the pandemic and to begin envisaging a post-pandemic musical landscape. The struggles to maintain connection and the unquantifiable intimacies of exchange that characterize live music at its best are counterpoised against, but also enacted via, the new necrophonics––or sounds made within, and in spite of, moribund, dying spaces––the pandemic has exposed. Improvisation, in this context, becomes even more salient as a practice of adaptation and resistance to the newly emergent norms. This volume is a start at assembling diverse voices that move from first principles to direct action, and we emphasize the remarkable scope of pragmatic, grassroots solutions proposed by contributors across a significant range of voices and experiences. We argue for a fundamental first principle in which direct actions that support the allocation of resources to the creative commons be lateralized to avoid top-down forms that limit access to, and use of, precious public commons resources.